2023
DOI: 10.3389/fnut.2023.1172610
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of fat-free mass index and appendicular skeletal muscle mass index in cancer malnutrition: a propensity score match analysis

Abstract: BackgroundReduced muscle mass (RMM) is a phenotypic criterion for malnutrition; the appendicular skeletal muscle mass index (ASMI) and fat-free mass index (FFMI) are both applicable indicators in the global leadership initiative on malnutrition (GLIM) guideline. However, their sensitivity and prognostic effect remain unclear.MethodsClinical data of 2,477 patients with malignant tumors were collected. Multi-frequency bioelectrical impedance analysis was used to obtain ASMI and FFMI. RMM was confirmed by ASMI (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For anthropometric assessment, weight, height, and two skinfolds (triceps brachii and suprailiac, respectively) were measured according to criteria accepted by certified International Society for the Advancement of Anthropometry (ISAK) level 1 experts 20,21 . Skinfold calipers are commonly used instruments for skinfold thickness measurement 36,37 . Studies have shown that skinfold thickness is associated with the nutritional health status of the human body 38–40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For anthropometric assessment, weight, height, and two skinfolds (triceps brachii and suprailiac, respectively) were measured according to criteria accepted by certified International Society for the Advancement of Anthropometry (ISAK) level 1 experts 20,21 . Skinfold calipers are commonly used instruments for skinfold thickness measurement 36,37 . Studies have shown that skinfold thickness is associated with the nutritional health status of the human body 38–40 .…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Skinfold calipers are commonly used instruments for skinfold thickness measurement. 36,37 TA B L E 3 Relevant information of port catheterization in the two groups. Studies have shown that skinfold thickness is associated with the nutritional health status of the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition has been studied in many pathologies, but not so much in heterogeneous hospitalized patients of different ages. In the study by Ji et al [ 11 ], they found that reduced muscle mass determined by ASMI in cancer patients was associated with worse survival. Cereda et al [ 10 ] analyzed the FFM index (FFMI) in a cohort of cancer patients, observing that patients with a decreased FFMI had higher mortality and lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A mortality of 17.3% of the total sample was observed at 6 months, 7.5% of early readmission and a median stay of 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days.…”
Section: Association Between Prognostic Clinical Outcomes and Cipa Re...mentioning
confidence: 99%
See 1 more Smart Citation